Metered Dose Inhalers (MDI) vs. Nebulizer for Asthma Management: A Comparative Analysis of Adherence and Patient Satisfaction - Seddek, Nermien Helmy; Sardidi , Nada Sami; Alabkari, Alaa; Al-hamzah, Fatimah; Al-Yusuf, Naba; Alali, Saleel; Al-Khulayf , Zainab (Journal of Posthumanism, 2026)
Introduction: Asthma is a common chronic inflammatory airway disease affecting millions worldwide and represents a significant public health burden, including in Saudi Arabia. Inhaled therapies via devices like MDIs and nebulizers are the cornerstone of treatment as they deliver medication directly to the lungs with minimal systemic effects. Although both have comparable inhalation techniques, adherence is known to significantly influence outcomes. Furthermore, patient satisfaction is strongly linked to adherence, asthma control, and quality of life. Objectives: To compare bronchodilator delivery using MDIs versus nebulizers in adult asthma patients, focusing on adherence and satisfaction. Additionally, the study compared the user-friendliness of MDIs and nebulizers among asthmatic patients. Methodology: A cross-sectional study assessed adherence and satisfaction using an online questionnaire distributed via social media. Adult asthma patients (18–65 years) from the Eastern Province of Saudi Arabia were included, while COPD patients, pediatric cases, non-residents, and DPI users were excluded. Of 303 responses, 273 were analyzed. The questionnaire was adapted from validated tools (ACT, AQLQ, ASUI) with added items on usability, satisfaction, and adherence. Data were analyzed using SPSS version 29 with descriptive statistics and group comparisons. Results: Patients using nebulizers only demonstrated less adherence compared to only MDI users. Difficulty using and discontinuation due to cost were found to be the significant factors. For satisfaction, only MDI users also demonstrated relatively high satisfaction compared to only nebulizer users, particularly due to inhaler portability and confidence in use, which also make the MDI more user-friendly. Meanwhile, patients using both devices showed the highest adherence and satisfaction. Conclusion: Both MDIs and nebulizers are used among asthma patients; however, adherence and satisfaction depend mainly on several factors. Findings suggest usability, cost, and friendly use are found to be the key factors. Using both devices may provide flexibility, allow adjustment and improve consistency of use.